Instagram Reels as a Branding Medium - Ita Suryani; Intan Leliana; Yusuf Setiyawan (Persepsi: Communication Journal, 2022)
Instagram is a social platform utilized by most citizens including older people, adults to teenagers. It can grow engagement with the readers. It also functions as a branding medium to build branding or image of certain person, business, product, and company/institution. Branding is an effort to build an image in the eyes of the public. Instagram develops many innovations as one of which is creating the Instagram Reels feature. One of the purposes of using Instagram Reels is as a medium for personal, product, corporate, destination, and city and national branding. The purpose of this study is to find out how the Reels Instagram feature can be used as a medium for branding companies / agencies / personal / cities / regions with the aim of building or managing reputation. The research used the case study method where the data was taken from various sources with various tools. The results show that the Reels Instagram feature can be used as a medium for branding companies/agencies/personal/products/cities/regions with the aim of building or managing reputation. This can be a benchmark in attracting the attention / interest of Instagram users to view video reels repeatedly, therefore awareness and engagement is built.